Some problematic issues of the study of trasyanka: some results of the Oldenburg project - Zaprudski, Siarhiej M. (Journal of the Belarusian State University. Philology, 2022)
The article deals with problems of the identification of trasyanka with regard to the existing discourse, primarily in connection with the concluding article «Eleven questions and answers about the Belarusian-Russian mixed speech (“Trasyanka”)» published by Gerd Hentschel, head of the Oldenburg project for the study of the Belarusian-Russian mixed speech. Terminology used in the area of research, definitions of trasyanka, the problem of its coming into existence, as well as research methods are discussed. At the final stage of the project the key term was changed. The term «trasyanka» was replaced with the expression «Belarusian-Russian mixed speech» which had some dubious results since the latter concept is too broad. The object of producing a common definition of trasyanka was not set during the development of the linguistic part of the project, which narrowed the heuristic potential of this part. The postulated emergence of trasyanka in the 18th century, which is rightly disputed by the leader of the Oldenburg project, raises doubts due to the lack of reliable information about the Belarusian language as used at the end of the 18th ‒ 19th century, and by other methodological difficulties associated with the fact that Belarusian language did not have a stable form and was found in permanent dynamics during this and especially subsequent periods. The very definition of a certain type of the Belarusian speech as a mixed one given by either the scientific community or any significant social group could appear no earlier than the establishment of a discourse on literary languages with its inherent concept of norm, the emergence and socialisation of the culture of speech discipline, as well as a more or less developed national consciousness. In the process of developing methods for the linguistic qualification of the language material by means of the quantitative methodology, which by itself was an obvious achievement of the project, the necessity to take into account – simultaneously and «inclusively» – all main parameters related to different language levels became a problematic aspect. The qualification of the language material was largely based on the existing normative and, as a result, ideologised representations of the Belarusian language and as such was not fully adapted to the sociological part of the project. At present, due to a variety of reasons, a complete exploration of the sociological part of the project by Belarusian linguists is hardly possible.
Keywords: trasyanka; mixed speech variety; scientific discourse about trasyanka; language contact; Belarusian language; Russian language; Oldenburg project on the Belarusian-Russian mixed speech; Gerd Hentschel